Effect of Ocimum sanctum leaf on pathology of Escherichia coli infection in broiler chickens - KUMARI, M; GUPTA, R P; SHARMA, A (The Indian Journal of Animal Sciences, 2014)
The present study was undertaken to investigate the effect of Ocimum sanctum leaf powder on experimental Escherichia coli infection in broiler chickens. Day-old broiler chicks (160) were divided into 2 groups. The birds of group A were supplemented with dried O. sanctum leaf (OSL) powder in feed @5g/kg and the birds of group B were given feed without OSL supplementation. After 7 days of age, each bird in group A1 and B1 was inoculated with E. coli O78 (@107 CFU/0.5 ml) by the intraperitoneal route, whereas groups A2 and B2 were kept as controls. Mortality in group B1 was 35.56% whereas mortality was comparatively low (20%) in OSL supplemented group A1. There was no mortality in the control groups (A2 and B2). Gross lesions produced in group B1 were fibrinous mass on the surface of liver and heart, congestion in visceral organs, peritonitis, reddish intestinal mucosa and atrophy of bursa of Fabricius. The gross lesions in OSL supplemented infected group were of less intensity at different intervals as compared to those observed in non-supplemented infected group. Histopathological lesions observed were fibrinous pericarditis, myocarditis, fibrinous perihepatitis, haemorrhagic enteritis, proventriculitis and depletion of lymphocytes in bursa of Fabricius. In OSL supplemented E. coli infected group lesions were less severe in magnitude and lasted for shorter duration as compared to non-supplemented E.coli infected group, indicating reduction in severity of the disease and early recovery due to OSL supplementation.